THE INFLUENCE OF LEADERSHIP STYLE ON EMPLOYEE PERFORMANCE AT PT. WORKS OF HEVEA INDONESIA WITH WORK DISCIPLINE AS A VARIABLE INTERVENING - Purnama Sari, Dian; Syarifuddin, Shofian; Hanindiya, Beta; Mustaruddin, Mustaruddin; Sanjaya, Muhartri (Universitas Efarina, 2022)
This study aims to determineThe Effect of Leadership Style on Employee Performance at Pt. Karya Hevea Indonesia With Work Discipline As Intervening Variable. Based on 1)it can be seen that tcount (4.363) > ttable (1.701), as well as with a significance value of 0.00 <0.05, it can be concluded that the first hypothesis is accepted, meaning that the Leadership Style variable(X) positive and significant effecton Work Discipline (Y1). 2) it can be seen that tcount (1.917) > ttable (1.701), and a significance value of 0.00 <0.05, it can be concluded that the second hypothesis is accepted, meaning that Leadership Style(X) positive and significant effecton Employee Performance (Y2). 3) it can be seen that tcount (2.504) > ttable (1.701), and the significance value is 0.00 <0.05, it can be concluded that the third hypothesis is accepted, meaning Work Discipline (Y1)influentialpositive andsignificanton Employee Performance (Y2). 4) the direct effect of variable X on variable Y2 is 0.200. While the indirect effect through the Y1 variable is 0.636 x 0.329 = 0.2092, the results of the calculations show that the direct effect through the X variable is smaller than the indirect effect on the Y2 variable.